The Influence of Return on Assets, Return on Equity, Net Profit Margin, and Debt to Equity Ratio on the Stock Prices of Banking Companies on the Indonesia Stock Exchange (2023–2025) - Rodyah Widyarini; Silvia Hendrayanti (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the significance of the effect of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Debt to Equity Ratio (DER) on the stock prices of banking companies listed on the Indonesia Stock Exchange for the period 2023–2025. This study relies on secondary data as its primary data source. The research sample comprises 36 banking firms, which were determined through a purposive sampling approach. The research employs a documentation-based approach for data gathering. To examine the data, several analytical procedures were applied, encompassing tests for classical assumptions, multiple linear regression analysis, partial significance testing through the t-statistic, simultaneous significance evaluation via the F-statistic, and the coefficient of determination to assess model fit. The results conclude that ROA has no significant effect on stock prices; ROE has a significant effect on stock prices; NPM has no significant effect on stock prices; and DER has no significant effect on stock prices. Meanwhile, ROA, ROE, NPM, and DER simultaneously have a significant effect on the stock prices of banking companies listed on the Indonesia Stock Exchange for the period 2023–2025.